2014
DOI: 10.1007/s11896-014-9144-3
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Confession: Relating False Confession, Interrogative Compliance, Personality Traits, and Psychopathy

Abstract: The present study further supports the established notion that personality traits contribute to the phenomenon of false confessions and compliance in an interrogative setting. Furthermore, the study provides an investigation into the more recent interest in the potential effect of psychopathic traits in this context. A sample of university students (N = 607) completed questionnaires measuring psychopathic traits, interrogative compliance, and the big five personality factors. Of these, only 4.9% (n=30) claimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…What is known, however, is that interrogations are cognitively and emotionally demanding for those who conduct them (Kleider-Offutt et al 2016). Though previous research has identified a number of individual differences in intelligence and personality that are important in other, similarly demanding, law-enforcement contexts (Larmour et al 2015), none has been investigated with respect to effective interrogator performance (e.g. Alison et al 2013b;Kleider et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…What is known, however, is that interrogations are cognitively and emotionally demanding for those who conduct them (Kleider-Offutt et al 2016). Though previous research has identified a number of individual differences in intelligence and personality that are important in other, similarly demanding, law-enforcement contexts (Larmour et al 2015), none has been investigated with respect to effective interrogator performance (e.g. Alison et al 2013b;Kleider et al 2010).…”
Section: Introductionmentioning
confidence: 99%